1991
DOI: 10.1111/j.1439-0485.1991.tb00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Tackling the Sulfide Gradient: A Novel Strategy Involving Marine Nematodes and Chemoautotrophic Ectosymbionts

Abstract: Abstract. The Stilbonemutinue (marine free‐living nematodes) arc remarkable for cctosymbiotic bacteria, which cover the greatest part of their body in a highly ordered and species specific pattern. Using SEM we describe the main types of symbiotic cover and give evidence for the role of the bacteria in the nutrition of their host on the basis of stable carbon isotope ratios. In experimental systems the worms migrated repeatedly across a sulfide gradient during 12 h when sulfide concentrations were low, but st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
1
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(122 citation statements)
references
References 26 publications
3
117
1
1
Order By: Relevance
“…Arguments in favor of the hypothesis are given by pointing to the similarities between intestinal and ectosymbiontic microbes (e.g. Jensen 1987b) and to stages of lysis in the intestine (Ott and Novak 1989;Ott et al 1991). Jensen et al (1992) consider that digestion occurs in the posterior part of the gut.…”
Section: Ecologymentioning
confidence: 99%
See 3 more Smart Citations
“…Arguments in favor of the hypothesis are given by pointing to the similarities between intestinal and ectosymbiontic microbes (e.g. Jensen 1987b) and to stages of lysis in the intestine (Ott and Novak 1989;Ott et al 1991). Jensen et al (1992) consider that digestion occurs in the posterior part of the gut.…”
Section: Ecologymentioning
confidence: 99%
“…According to observations on the vertical distribution of Caribbean Stilbonematinae (Laxus oneistus; Ott et al 1995) in laboratory experiments, these nematodes expose their symbionts alternately to reducing or oxidizing conditions by migrations through the chemocline in both directions (Ott et al 1991). Another strategy for providing sulfide oxidizing ectosymbionts with suitable environmental conditions has been suggested by Ott et al (1998) and modified by Vopel et al (2001) for a sedentary, feather-shaped, colonial peritrich ciliate that expands into oxygenated water and contracts into sulfidic water close to the substrate.…”
Section: Ecologymentioning
confidence: 99%
See 2 more Smart Citations
“…Rosenberg et aL, (1991) observed that infaunal animals moved away in search of oxygen or to escape from hydrogen sulphide. The ecological potential of habitats exposed to sulphide can only be utilized by those organisms that are physiologically adapted to such hostile conditions which means that they cannot only cope with exposition to lasting hypoxia or even anoxia, but also with exposition to toxic and highly permeable hydrogen sulphide (Powell, 1989;Ott et aL, 1991). In organically enriched (but not overloaded) sediments, biological activities of infauna can promote the decomposition of organic matter and the oxidation of sulphides (Chareonpanish et aL, 1993).…”
Section: Impact On the Meiofaunamentioning
confidence: 99%